Vector Form Implementation in Three-Phase Power Flow Analysis Based on Power Injection Rectangular Coordinate - Lukmanul Hakim; Fandi Prayoga; Khairudin Khairudin; Herri Gusmedi (Jurusan Teknik Elektro Universitas Andalas, 2019)
This paper aims to propose the vector form implementation into three-phase power flow analysis. The developed algorithm is based on Newton-Raphson method with voltage is represented in rectangular coordinate. The Python programming language and its mathematical libraries are used in this works. Three-phase power flow analysis in vector form utilizes sparse matrix ordering algorithm, so the elements of the coefficient correction matrix can be rearranged easily. This method was used to solve three-phase power flow for balance or unbalance network in two actual distribution system feeders in Lampung, i.e. 119 nodes and 191 nodes. Comparison with traditional Newton-Raphson method (non-vector) shows the vector form is able to solve computation up to eight times faster than non-vector. Keywords: Three-phase power flow, Vector form, Newton-Raphson, Rectangular, Python